Effect of An Additional Amount of Fish and Fermentation Time on The Sensory Properties of The Lemea - Aziz, Abdul; Aji, Oktira Roka (Journal of Biotechnology and Natural Science, 2023)
Lemea, a traditional fermented food of the Rejang people in Bengkulu, is made from young bamboo and fish. The fish commonly used in the making Lemea is Mozambique tilapia or Mujair (Oreochromis mossambicus). The fermentation process typically lasts between 3 to 7 days. This study aimed to assess the sensory characteristics, including taste, color, texture, and aroma, of Lemea, based on the preferences of panelists. The variations examined were fermentation duration, and the amount of Mujair fish added. The research followed a completely randomized design, incorporating three fermentation durations (24, 96, and 144 hours) and three fish quantities (250 grams, 500 grams, and 750 grams). Sensory evaluations were conducted on the fermented samples, encompassing taste, aroma, texture, and color. The data revealed that the most favored taste and texture of Lemea were achieved with 500 grams of fish and a fermentation duration of 144 hours (J2W3). Likewise, the preferred aroma and color were observed in the sample with 750 grams of fish and 24 hours of fermentation (J3W1). The data analysis indicated that the sample with 500 grams of fish and a fermentation duration of 144 hours (J2W3) exhibited the most favorable sensory characteristics (taste, aroma, texture, and color). Thus, the quantity of fish added and the duration of fermentation influenced the sensory attributes of Lemea.